Older adults’ perspectives on physical activity and sedentary behaviour within their home using socio-ecological model - Naureen Naureen (PLOS ONE, 2023)
BackgroundThere are few studies that focus explicitly on the impact of the home environment on older adults’ sedentary behaviour (SB) and physical activity (PA) using the socio-ecological model (SEM). This study aims to investigate older adults’ PA and SB within the home environment integrating the SEM as a theoretical framework.MethodsA qualitative exploratory research design was employed to conduct 33 in-depth interviews (IDIs) and five focus group (FGs; n = 16) with multi-diverse ethnic older adults (mean age 72±5 years). Using reflexive thematic analysis themes were generated from the data set and were interpreted using the SEM.ResultsThe findings indicate that different levels of the SEM had an impact on older adults’ PA and SB. These include the 1) Individual level: Attitude, perception and motivation 2) Interpersonal level: Family and Friends: a motive to remain active 3) Organisational level: healthcare institutes, 4) Community level factors: Significance of social groups, 5) Physical Environment: Microenvironment and 6) Policy level factors (lockdown restrictions and healthcare system). This model can be utilised to foster activity within the home by focusing on the facilitators and barriers identified at each of these levels of influence.ConclusionThe study findings suggest that modifying PA and SB in the home environment is complex and is influenced across different levels of the SEM. Therefore, a holistic approach is required that integrates these multiple influences. This understanding can inform the design of interventions that seek to optimize PA and minimize SB within the home environment.